2003
DOI: 10.1023/a:1020695923788
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The mode of action of the anti-fungal compounds, 1,10-phenanthroline (phen), [Cu(phen)2(mal)] x 2H2O, [Mn(phen)2(mal)] x 2H2O and [Ag2(phen)3(mal)] x 2H2O (malH2 = malonic acid), was examined using the pathogenic yeast Candida albicans. The compounds have minimum inhibitory concentrations (MIC's) in the range 1.25-5.0 microg cm(-3) and at a concentration of 10 microg cm(-3) display some fungicidal activity. Yeast cells exposed to these drugs show a diminished ability to reduce 2,3,5-triphenyltetrazolium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 19 publications
5
75
0
Order By: Relevance
“…Complex 5 exhibits the greatest fungitoxic activity and indeed is comparable to the prescription drug ketoconazole at this concentration. Preliminary studies on the mode of action of the copper TBZH complexes have revealed that they cause a reduction in the ergosterol content of the fungal cells [30] which was also found to be the case for the phenanthroline complexes previously reported [20].…”
Section: Biological Activitiesmentioning
confidence: 67%
See 1 more Smart Citation
“…Complex 5 exhibits the greatest fungitoxic activity and indeed is comparable to the prescription drug ketoconazole at this concentration. Preliminary studies on the mode of action of the copper TBZH complexes have revealed that they cause a reduction in the ergosterol content of the fungal cells [30] which was also found to be the case for the phenanthroline complexes previously reported [20].…”
Section: Biological Activitiesmentioning
confidence: 67%
“…The mode of action of 1,10-phenanthroline and a number of our potent anti-candida metal complexes {M ¼ Cu(II), Mn(II) or Ag(I)} [20] was examined. The phen and its metal complexes had minimum inhibitory concentrations (MICs) in the range 1.25-5 lg/ml and at concentration of 10 lg/ml they displayed some fungicidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are the complexes [Cu(phen) 2 mal)]•2H 2 O and [Ag 2 (phen) 2 (mal)]•2H 2 O (phen = 1,10-phenanthroline, malH 2 = malonic acid) reported by B. Coyle et al which inhibit the growth of Candida albicans [8].…”
Section: Introductionmentioning
confidence: 99%
“…The photochemical and redox properties of complexes can be varied systematically through appropriate substitution on the phenanthroline rings [15][16][17]. 1,10-Phenanthroline, as well as some of its derived complexes, do exhibit antimicrobial properties [18,19].…”
Section: Introductionmentioning
confidence: 99%